Pengaruh Disiplin Kerja dan Komitmen Organisasi terhadap Produktivitas Kerja Pegawai di Inspektorat Daerah Provinsi Sulawesi Selatan - Andi Siti Nurhaliza ZL; Anwar Ramli; Uhud Darmawan Natsir; Romansyah Sahabuddin; Burhanuddin Burhanuddin (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study aims to analyze the influence of work discipline and organizational commitment on employee work productivity at the Regional Inspectorate of South Sulawesi Province. This research employs a quantitative approach using a proportionate stratified random sampling technique, involving 99 functional employees as respondents. Data were collected through a structured questionnaire based on a Likert scale, which measures variables related to work discipline, organizational commitment, and employee productivity. The collected data were then analyzed using multiple linear regression with the assistance of SPSS version 27 to determine the relationships and significance levels among the variables.The results of the study reveal that work discipline has a positive and significant effect on employee work productivity, indicating that higher levels of discipline contribute to improved performance outcomes. Similarly, organizational commitment also demonstrates a positive and significant influence on productivity, suggesting that employees with stronger attachment and loyalty to the organization tend to perform better. Furthermore, the simultaneous test results show that both work discipline and organizational commitment collectively have a significant impact on employee productivity. These findings highlight the importance of strengthening disciplinary practices and fostering organizational commitment to enhance overall employee performance. Therefore, organizations, particularly public sector institutions, are encouraged to implement policies and strategies that support these factors to achieve optimal productivity levels.